Pengaruh Pemanfaatan Media Digital terhadap Motivasi Belajar Siswa Kelas XI SMA - Andi Muhammad Mahfud; Muhammad Idris; Muhammad Asdar; Muhlis; Rezha Arfiani; Sri Wahyuni; Julita; Nanna Fitriani; Hasniar; Karmenita; Anita Ramadhani; Novita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effect of using digital media on the learning motivation of grade XI senior high school students. The rapid development of technology has changed the way learning is carried out in schools and encouraged teachers to use digital media such as learning videos, interactive presentations, and online learning platforms. This study used a descriptive qualitative approach through observation, interviews, and documentation during the PLP program in class XI. The results show that digital media helps create a more attractive learning atmosphere, increases students’ attention, and encourages active participation in class. Students also become more enthusiastic in understanding the material because the presentation of content is more visual, practical, and easy to follow.